UPDATE REVIEW OF PHYSALIS: ETHNOGRAPHY VALUE AND ITS USEFULNESS IN STROKE ISCHEMIC DISEASE - Feda Makkiyah (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
One Indonesian herbal medicine that deserves attention is Physalis minimal Linn. Identifying medications and their use in the correct dosages is crucial for effective treatment. Country gooseberry, or Physalis minima Linn, has anti-cancer, anti-diabetic, analgesic, antipyretic, and anti-inflammatory properties. This paper aims to reveal the potential use of Physalis minima Linn in stroke ischemic disease, a substantial current health issue in Indonesia. We used Scopus and Google databases to screen the intended articles with keywords used are TITLE-ABS- KEY (stroke) AND physalis AND antioxidant OR antiinflammation, "Physalis minima" and stroke ischemic" and "thrombolytic" OR " Antiinflammatory" OR "Antioxidant". Two other fellow researchers screened the resulting articles and read the articles together, and resumed the narration. Ten articles resulted in the screening—however, only 1 article was included in this article from the Scopus Databases. However, we got five articles out of 10 articles from Google databases. We divided the narration based on several items, such as anti-thrombolytic effects, antioxidant and antiinflammation, and ethnography of the plant. Conclusions. Physalis minima have its potency to be explored as an alternative treatment to stroke ischemic. Firstly P.minima tends to thrombolytic clot in case of thrombosis in stroke ischemia. Secondly, P.minima have an effect of antioxidants and anti-inflammation that is useful in acute stroke ischemia.